Hydrogen Production from Biomass Wastes by Chemical-Milling-Heating Method - Kanatip Kumproa (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The objective of the research aims to study the effects of NH4OH concentration in lignin extraction and HCl concentration in acid hydrolysis on lignin and hemicelluloses contents respectively. In addition, the research aims to investigate the effects of Ni(OH)2 as a catalyst, Ca(OH)2 as a CO2 capture agent and milling time on H2 concentration in gaseous products and the effect of milling time on milled mixtures and heated mixture. The research includes production of high-purity hydrogen gas from rice husk, rice straw, sugarcane bagasse, and sugarcane leaves by a three-step process. The samples were characterized by the ultimate analysis, proximate analysis, UV-spectrophotometry, scanning electron microscopy (SEM) with energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), thermogravimetry-mass spectrometry (TG/MS), and particle size analysis. The gaseous products were analyzed by gas chromatography (GC). The results revealed that the high-purity hydrogen gas can be produced from raw materials (rice husk, rice straw, sugarcane bagasse and sugarcane leaves) in the three-step process without separation process. The ultimate and proximate analysis showed the suitability of raw materials in hydrogen gas production. The UV spectrophotometric results revealed that the highest lignin and hemicellulose contents from rice husk, rice straw, sugarcane bagasse, and sugarcane leaves were achieved by applying 10 %v/v of NH4OH solution at room temperature for 24 h and 4-6 %v/v of HCl solution at 100oC for 5 h by acid hydrolysis. According to SEM images and EDS point analysis of raw materials, the cell wall of raw materials consists of lignin, covering on cellulose fibers. Cellulose fibers were separated from cell wall by removing lignin following with acid hydrolysis of hemicellulose. In addition, SiO2 is highly concentrated on cell wall of raw materials. Chemical treatment can separate cell wall in order to reduce the amount of SiO2. The TG/MS results of the milled raw materials/Ni(OH)2/Ca(OH)2 mixtures showed that the gaseous product consists of H2, H2O, CH4, CO and CO2. Moreover, H2/CH4 and CO/CO2 emitted at about 400oC and 650oC, respectively. Therefore, the optimum temperature for collecting hydrogen gas in this research is 600oC. Additionally, the amount of hydrogen gas emission increased with the increasing the milling times, which were 0, 15, 30, 60 and 120 min, respectively. The yield of H2 emission from the mixtures with Ni(OH)2 as the catalyst were higher than the yield of H2 emission from the mixtures without Ni(OH)2. The particle size analysis showed that the average particle size of the milled mixtures decreased with the increasing milling times, which were 0, 15, 30, 60 and 120 min, respectively. According to XRD patterns of the milled mixtures, it indicated that no solid state reaction occurred during mechanochemical treatment. The mixtures are highly amorphous state. The XRD pattern of the heated mixtures showing the appearance of Ni and CaCO3 peaks indicated the occurrence of the reduction of NiO to produce Ni and the carbonation of CaO to reduce CO2. In addition, FT-IR results of heated mixtures indicated that organic compounds from biomass decomposed by gasification. The GC result showed that the highest H2 concentration from the raw materials were approximately 95-97 %mol. Furthermore, the highest H2 concentration from different raw materials were achieved by applying the mechanochemical treatment of raw materials with Ni(OH)2 as the catalyst and Ca(OH)2 as the CO2 capture agent at 700 rpm of milling speed for 60-120 min of milling time and then heated at 600oC for 60 min by gasification. For the case of raw materials with Ni(CH3COO)2/CH3COONa and H2O mixtures, the XRD pattern of the heated mixtures showed the appearance of Ni and Na2CO3 peaks. It indicated that the reduction of Ni(CH3COO)2 in producing Ni as the catalyst and the reaction of CH3COONa and steam could produce CH4 as a starting material for H2 production were occurred. Additionally, the GC results showed that the highest H2 concentration of raw materials were approximately 97 %mol, which were achieved by applying the mechanochemical treatment of raw materials with Ni(CH3COO)2/CH3COONa as the catalysts and 4.5 cm3 of H2O as the precursor at 300 rpm of milling speed for 60 min of milling time and then heated at 600oC for 60 min by gasification.